The Language Assessment In Teaching-Learning English - Winna, Winna; Sabarun, Sabarun (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Languages assesment is the process of determining an individual's degree of language ability by use of standardized tests and observations. It is a crucial component of English teaching and learning since it enables teachers and students to receive insightful feedback while also tracking the student's development over time. There are various kinds of language assessment which can be assist educators in adapting their instructional approaches to meet the needs of learners effectively. The objective of this research is to an overview language assessment and to find kinds of assessment. The method of this research used library research. Object of this research are books, journal and article. Based on the research data, language assessment is an essential component of both teaching and learning English, and kinds of language assessment consist of (1)informal and formal assessment, (2)formative and summative assessment, (3)perfomanace-based assessment, (4)achievement assessment, (5)diagnostic assessment, (6)placement assessment, (7)profiency assessment, and (8)aptitude assessment.